Functional Characterization of Acinetobacter baumannii Lacking the RNA Chaperone Hfq - Kuo, Han-Yueh; Chao, Hsuan-Hao; Liao, Po-Cheng; Hsu, Long; Chang, Kai-Chih; Tung, Chi-Hua; Chen, Chang-Hua; Liou, Ming-Li (Frontiers in Microbiology, 2017)
The RNA chaperone Hfq is involved in the riboregulation of diverse genes via small RNAs. Recent studies have demonstrated that Hfq contributes to the stress response and the virulence of several pathogens, and the roles of Hfq vary among bacterial species. Here, we attempted to elucidate the role of Hfq in Acinetobacter baumannii ATCC 17978. In the absence of hfq, A. baumannii exhibited retarded cell growth and was highly sensitive to environmental stress, including osmotic and oxidative pressure, pH and temperature. Compared to the wild type, the Hfq mutant had reduced outer membrane vesicles secretion and fimbriae production as visualized by atomic force microscopy. The absence of hfq reduced biofilm formation, airway epithelial cell adhesion and invasion, and survival in macrophage. Further, the hfq mutant induced significantly higher IL-8 levels in airway epithelial cells, which would promote bacterial clearance by the host. In addition to results similar to those reported for other bacteria, our findings demonstrate that Hfq is required in the regulation of the iron-acquisition system via down-regulating the bauA and basD genes, the stress-related outer membrane proteins carO, A1S_0820, ompA and nlpE, and the stress-related cytosolic proteins uspA, and groEL. Our data indicate that Hfq plays a critical role in environmental adaptation and virulence in A. baumannii by modulating stress responses, surface architectures, and virulence factors. This study is the first to illustrate the functional role of Hfq in A. baumannii.